Viola suavis subsp. naqshii: a new taxon from Kashmir Himalaya, India - Ganie, Aijaz H.; Islam, Tajamul (Phytotaxa, 2023)
Viola suavis subsp. naqshii (Violaceae) from Kashmir Himalaya, India is described here. The new taxon is based on characters like linear-lanceolate stipules with long fimbriae, position of bracteoles on peduncle and curved nature of the spur. Comparison of diagnostic characters of this new taxon with closely related taxa and photo-illustrations are also provided to facilitate field identification.